2005
DOI: 10.1002/ana.20547
|View full text |Cite
|
Sign up to set email alerts
|

Xenon and hypothermia combine to provide neuroprotection from neonatal asphyxia

Abstract: Perinatal asphyxia can result in neuronal injury with long-term neurological and behavioral consequences. Although hypothermia may provide some modest benefit, the intervention itself can produce adverse consequences. We have investigated whether xenon, an antagonist of the N-methyl-D-aspartate subtype of the glutamate receptor, can enhance the neuroprotection provided by mild hypothermia. Cultured neurons injured by oxygen-glucose deprivation were protected by combinations of interventions of xenon and hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
193
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(212 citation statements)
references
References 49 publications
12
193
1
6
Order By: Relevance
“…The maximum safe concentration of inhaled xenon has been suggested to be less than one minimum alveolar concentration (MAC) on hippocampal slices from 7-d-old rats (24). A concentration of 50% xenon used in this study is equivalent to about 1/3MAC in rats (25) or 0.7MAC in humans (26) which is well within the range of proposed safe concentrations as well as being within the effective neonatal neuroprotective range (13,15,20).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The maximum safe concentration of inhaled xenon has been suggested to be less than one minimum alveolar concentration (MAC) on hippocampal slices from 7-d-old rats (24). A concentration of 50% xenon used in this study is equivalent to about 1/3MAC in rats (25) or 0.7MAC in humans (26) which is well within the range of proposed safe concentrations as well as being within the effective neonatal neuroprotective range (13,15,20).…”
Section: Discussionmentioning
confidence: 61%
“…Xenon has proven to be neuroprotective both in vivo and in vitro with minimal adverse effects (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). We and others have previously reported that adding immediate xenon to HT enhanced the neuroprotective effects of HT after induced hypoxia-ischemia in neonatal rats (12,13,15,20) and newborn pigs (21). In neonatal rats, xenon, when added to immediate hypothermia, either immediately or after a 2 h delay, increases neuroprotection (20).…”
mentioning
confidence: 98%
“…This combination has the potential to improve the otherwise bleak outcome after perinatal asphyxia. Considering that HT is currently becoming standard of care after HI injury in both adults after cardiac arrest (Polderman, 2008) and newborns after perinatal asphyxia (Hoehn et al, 2008) and that Xe significantly enhances this effect (Dingley et al, 2006;Hobbs et al, 2008a;Ma et al, 2005;Martin et al, 2007), we have compared three different Xe delivery strategies in combination with the established HT treatment. As Xe is very expensive and is likely only to be delivered in specialist centers for combination with HT, patient transport is required and two important questions arise:…”
Section: Discussionmentioning
confidence: 99%
“…The left common carotid artery was cut between double ligatures of 6.0 silk sutures. After < 90 mins recovery with their dam, pups were exposed to 8% oxygen for 90 mins in a temperature-controlled chamber at a rectal temperature (T rect ) of 361C, which, without treatment, results in B60% unilateral brain injury in this model (Bona et al, 1998;Ma et al, 2005). The 102 pups that survived the insult (of which 4 were used for temperature monitoring) were then randomized, matched for sex (Table 1) and weight, and allowed to recover after the HI insult for 3 h at T rect 371C, or T rect 321C HT breathing 0% or 50% Xe for either 1 or 3 h. They were breathing either (i) air for the first 3 h at T rect 371C, (ii) air for the first 3 h at T rect 321C, (iii) 50% Xe for the first hour and air for the remaining 2 h at 321C (1 h Immediate Xe/3 h HT), or (iv) air for the initial 2 h followed by 50% Xe for the third, final hour at 321C (1 h Delayed Xe/3 h HT) ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation